Electoral Violence, Insecurity and the Credibility of the 2023 General Election in Nigeria - Yusuf, Abdulrahman Barau; Saminu, Auwalu (Kashere Journal of Politics and International Relations, 2023)
This paper assesses how electoral violence and insecurity affected the credibility of the 2023 general elections in Nigeria. The problem in this study is that insecurity and electoral violence are often used by politicians as tools to succeed in their political affairs. This can be in the form of organizing armed thugs to disrupt the electoral process by destroying election materials, attacks on the election staff, displacement and intimidation of voters, assassination of political opponents, innocent voters and election staff. In all political activities in Nigeria, violence and insecurity are reflected. These act of violence and insecurity started from the pre-election to post-election periods. This made success in conducting credible elections difficult in the country. The research method used is qualitative with a descriptive approach. Data collection was carried out using, participant observations, and literature studies. Triangulation method of data analysis was used. As for the results of this study, first, many of the political candidates use violence as a weapon to win elections, the violent nature of elections and the threats from certain terrorist groups, and bandits have succeeded in reducing the voter turnout as many are scared of endangering their physical well-being. Accordingly, some recommendations and policy implications became important. For instance, innovative security strategies and deployment for the protection of voters, election personnel, materials, as well as the general public became necessary for a credible election to hold.